Penerapan Sistem Pendukung Keputusan Dalam Penerimaan Sales Internet Provider Dengan Menggunakan Metode WASPAS dan Pembobotan ROC - Jeperson Hutahaean; Zulfi Azhar; Neni Mulyani; Ingrid Sartika Putriayu Sihite; Yohana Dela Vega (STMIK Budi Darma, 2023)
Internet sales provider is also one of the sales that is needed in a company engaged in this field. Because it is not easy to become sales. So with that a company is looking for sales that have some experience and can master work in that field. However, this acceptance is not easy to obtain because there are still many who do not have experience in this field. So with that in solving existing problems, several criteria are needed including Target, Attendance, Discipline, Creativity and Ability in Speaking. And in this research also really need a system where the system can solve existing problems. The system is a decision support system and is assisted by a method that will produce the right value, the method is the WASPAS and ROC methods. So with this, in accepting internet sales providers who have the highest results so that they will be accepted as internet sales providers, there is the ABT3 alternative on behalf of Andreas Francis with a total value of 2.41877